Pilot land of Biosoy new superior variety soybean for farmers in Wonoharjo Village, Boyolali Regency - Sumarmi, Sumarmi; Kholis, Awaludin Sinur; Sholihah, Efi Nikmatu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The area of soybean planting in Indonesia has decreased. The reduction in the land area causes a decrease in crop yields. Until now, 65% of the soybeans needed by the Indonesian people come from other countries, so the creation of new land needs to be tried and the number of farmers who are able to grow soybeans must be increased. Farmers in Wonoharjo village, Kemusu, Boyolali Regency are trained to grow soybeans. Land preparation is done by adding liquid fertilizer which contains a lot of nitrogen-fixing bacteria. 800 soybean seeds of Biosoy were planted with a spacing of 40 cm long and 20 cm wide. Biosoy's new high-yielding soybean seeds were selected to ensure a good harvest. Plant care by providing additional NPK fertilizer when soybeans are 40 days old, and cleaning weeds. Demonstration plot, lg 11 meters, a width of 4 meters with 400 growing points, produces 6.7 kilograms of dry soybeans from 200 grams of seed. The average number of pods per plant is 41 pieces. The average weight of 100 soybean seeds is 21.85 grams. The land that has never been planted with soybeans has succeeded as a Biosoy demonstration plot for farmers.